Mulher, memória e narrativas jusliterárias no encarceramento feminino - Bispo, Adele Caroline Santos (2025)
This dissertation analyzes the Brazilian penal system from the perspective of interdisciplinarity between Law and Literature to understand and analyze the rights violations suffered by incarcerated women through their memories and life narratives included in literary writing. Firstly, the unconstitutional state of affairs experienced by women incarcerated in the Brazilian prison system is analyzed through the Claim of Non-Compliance with Fundamental Precepts (ADPF) no. 347. Afterwards, using jurisprudence, the existing intersection is linked between literary narratives and women's life experience based on an analysis of the principle of human dignity in the face of female incarceration. Given the recognition of the importance of a feminist critical criminology, the question arises as to how the penal system has been used in a way that legitimizes the unconstitutionalities, inequalities and invisibility of women. It is also questioned how women in a context of oppression narrate their own experience, raising questions about the criminal justice system and the meaning of justice and female citizenship in the Democratic State of Law. We opt for an inductive, qualitative, theoretical, documentary, interdisciplinary methodology anchored in the phenomenological hermeneutic method with contributions from discourse analysis and critical criminology, linked to the research line Process of Constitutionalization of Rights and Citizenship: theoretical and methodological aspects.